Analisis Kualitas Air pada Genangan Air Hujan sebagai Konsumsi Hewan Ternak di Desa Teba Timur Kabupaten Timor Tengah Utara - Santiari, Made; Tuas, Maria Angelina (Bioscientist : Jurnal Ilmiah Biologi, 2021)
East Teba Village has limited water availability due to the relatively long duration of the dry season, so the villagers use rainwater puddles for various activities, including consumption (source of drinking water) for livestock. This study aims to determine the quality of water in puddles of rainwater for consumption (source of drinking water) livestock. This research is quantitative descriptive. The sampling point of the test is the point where livestock drink water. Sampling test based on SNI 6989.57:2008 regarding the method of sampling surface water. The test result data is compared with the quality standard and the quality status is calculated using the pollution index method. The results showed that the TSS value had exceeded the class 2 and class 3 quality standards, while the BOD value had exceeded the class 2 quality standard and still met the class 3 quality standard. The parameter index value obtained was 2.20 which was classified as lightly polluted. The water in the puddle cannot be consumed by livestock, because the water does not meet the quality standard based on the calculation of the quality status using the pollution index method.